Psychological Aspects in Children with Cleft Lip and/or Palate: a Brief Commentary on Some Relevant Findings for Health Teams - Marcos Roberto Tovani-Palone (Universidad Nacional de Córdoba, 2019)
Cleft lip and/or palate (CL/P) are among the most prevalent of all birth defects in human, affecting approximately 1:700 live births(1). The etiology of CL/P is thought to be multifactorial, involving an interaction between genetic and environmental factors (2,3).